Clinical Presentation and Outcome of Congenital Thoracic Malformations in Children Beyond Neonatal Period - Shazia Soomro, Misbah Anjum, Shazia Kulsoom, Safia Bibi, Pervez Ali, Bilquis Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To describe the clinical spectrum of presentation and outcome of children with congenital thoracic malformations beyond neonatal age. Methodology: Cross sectional study conducted at inpatient department of National institute of child health from Jan-Dec 2021. All patients hospitalized in study duration with diagnosis of congenital thoracic formations from 1 month till 12 years of age were enrolled. History, examination, laboratory tests, treatment and outcome were recorded. Results: Total 44 children were enrolled with mean age of 7.7+10.8 months. Common congenital thoracic malformations were congenital diaphragmatic hernia 24(54.5%), congenital cystic adenomatoid malformation 6(13.6%), congenital lobar emphysema5(11.4%) and eventration of diaphragm 4(9.1%). Three (6.9%) patients had associated cardiac anomalies. Surgical intervention was done in 33 (75%) patients with a postoperative survival rate of 95.4%. Conclusion: Congenital diaphragmatic hernia and cystic adenomatoid malformation are common congenital thoracic malformations that present beyond neonatal age and are associated with good postsurgical outcome. Keywords: congenital diaphragmatic hernia, congenital cystic adenomatoid malformation, beyond neonate